Fireside corrosion degradation of ferritic alloys at 600°C in oxy-fired conditions - Dudziak, Tomasz Pawel; Hussain, Tanvir; Simms, Nigel J.; Syed, Adnan U.; Oakey, John E. (Elsevier, 2013)
This paper reports the results of a study carried out to investigate the effects of simulated coal/biomass combustion conditions on the fireside corrosion. The 1000 h deposit recoat exposure (5 × 200 h cycles) was carried out at 600 °C. In these tests ferritic alloys were used 15Mo3, T22, T23 and T91. Kinetics data were generated for the alloys exposed using both traditional weight change methods and metal loss measurements. The highest rate of corrosion based on EDX results occurred under D1 deposit where provoke mainly by the formation of alkali iron tri-sulphate phase.
Keywords: A. Alloy; A. Steel; B. SEM; B. Energy dispersive x-ray spectroscopy; C. Atmospheric corrosion